The Theory of Savers' Rent and Some of Its Applications - Mixter, C. W. (Quarterly Journal of Economics, 1899)
Journal Article The Theory of Savers' Rent and Some of its Applications Get access C. W. Mixter C. W. Mixter Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 13, Issue 3, April 1899, Pages 245–269, https://doi.org/10.2307/1891104 Published: 01 April 1899